MEANING-LIFE ORIENTATIONS AMONG PEOPLE WITH PARENTAL DEPRIVATION IN CHILDHOOD - Tarjumanyan, Silvi (Modern Psychology, 2022)
The article discusses the results of our research on meaning-life orientations among people with parental deprivation. It is supposed that people who have had parental deprivation in childhood on the way to realizing the meaning of life have a number of problems with the existence of life goals, choices and evaluations of meanings. To illuminate this uncharted area, we have conducted a research. The purpose of the research was to find out the connection of the meaning of life with self-actualization among the people with childhood parental deprivation. In this article we will concentrate on the analysis of some experimental results, which will describe the peculiarities in the meaning-life orientations among deprived people. The article summarizes the findings and contributions made in our research. The main conclusion that can be drawn is that, though a lot of sources in literature show that people with parental deprivation have more difficulties in the process of realizing and forming meaning in their life, our study provides evidence that there are no differences in the orientations of meaning-life between deprived and non-deprived subjects. Broadly translated our findings indicate that parental deprivation does not have unaltered impact on the meaning of life of a deprived person.